The influence mechanism of the relationship between entrepreneurial learning and entrepreneurial intention - Lin, Cong; Pan, Yan; Yu, Yanli; Feng, Libo; Chen, Zhiyong (Frontiers in Psychology, 2023)
Based on relevant literature, this study adopted entrepreneurial learning theory to construct a relationship model between entrepreneurial learning and entrepreneurial intention. In this framework, entrepreneurial learning was divided into three dimensions: entrepreneurial education learning, experiential learning, and social network learning. A questionnaire survey was conducted among 1,399 undergraduate students in Zhejiang Province to investigate how entrepreneurial learning influenced entrepreneurial intention, while considering the mediating effect of entrepreneurial self-efficacy. This empirical research found that: (1) experiential learning and social network learning had significant positive impacts on entrepreneurial intention, but there was no significant relationship between entrepreneurial education learning and entrepreneurial intention; (2) entrepreneurship education learning and social network learning had significant positive relationships with entrepreneurial self-efficacy, but experiential learning had a significant negative relationship with entrepreneurial self-efficacy; and (3) entrepreneurial self-efficacy partially mediated the relationship between experiential learning, social network learning, and entrepreneurial intention, and fully mediated the relationship between entrepreneurial education learning and entrepreneurial intention. These findings suggest that colleges and universities in China could broaden entrepreneurial learning and strengthen social network learning.